Pengenalan Permainan Tradisional Galah Hadang Di Sekolah Dasar UPT SPF SD INPRES Tamangapa, Kelurahan Antang, Kecamatan Manggala, Kota Makassar - Nurhikmah; Saparuddin Latu; Dewi Nurliasari Yulis; Bellona Mardhatillah Sabillah; Muh. Khaedar; Nurcholis Panji Bayu Astra (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2025)
The traditional game galah hadang is a culturally grounded form of play that integrates movement, strategy, teamwork, and sportsmanship; however, its practice among elementary school children has tended to decline alongside shifts in play patterns and reduced opportunities for meaningful physical activity. This study aimed to (1) introduce galah hadang to Grade 5 students at UPT SPF SD Inpres Tamangapa Elementary School in Makassar and (2) assess changes in students’ gameplay performance following the introductory session. A quantitative pre-experimental one-group pretest–posttest design was implemented in a single meeting involving 20 Grade 5 students. Gameplay performance was assessed using a teacher-rated galah hadang test on a 1–5 scale across four indicators: accuracy in guarding the line, agility in evasion, rule compliance, and team cooperation, supported by activity documentation. The findings indicate improved performance across all indicators after a structured introduction that combined rule socialization, role simulation, and supervised practice, with the most prominent gains observed in rule compliance and team cooperation. These results suggest that a systematically delivered traditional-game introduction can serve as a practical physical education learning alternative to strengthen both motor-related skills and social play behaviors, while providing a feasible evaluation basis for school-based community engagement programs.